Revisión de los factores de riesgo y los programas de prevención de la lesión del ligamento cruzado anterior en fútbol femenino: propuesta de prevención - Romero-Moraleda, B.; Cuellar, A.; Gonzalez, J.; Bastida, N.; Echarri, E.; Gallardo, J.; Paredes, V. (Revista Internacional de Ciencias del Deporte, 2017)
The aims of this review were to analyce the causes and risk factors for ACL injury, a systematic review of current prevention programs and pose a protocol for preventing of ACL injury. Searches were performed in PubMed, PeDRO, and EBSCO data, taking into account keywords in DeCS and MeSH terms, which provided with 606 and 228 articles respectively. According to inclusion and exclusion criteria, 18 articles were selected for study. For any knee injury risk factors are a previous injury, fatigue and muscle strength imbalance between hamstrings and the quadriceps muscle (McCall y col., 2014). In the case of ACL injury studies focus on causes like the Q angle, the valgus knee, the genu recurvatum, the pronator foot and the external tibial torsion among others. In addition, the ACL of women is smaller in length and has smaller cross section than the ACL of men (Sutton y Bullock, 2013). Prevention programs included training the core, propioception, flexibility, motor control, learn technique and eccentric work (McCall y col., 2014; Myer y col., 2012; Stevenson y col., 2014; Sugimoto y col., 2014). In conclusion, the specific risk factors for this injury in women are presented with the effectiveness shown in the different preventive programs analyzed. The prevention programs analyzed include improvements for neuromuscular strength, stretching, plyometry, balance, core and correction of the technique of jump landing and changes of direction.